Establishing Shariah Audit Criteria for Zakat Operations: Where to Begin? - Mohd Suffian Mohamed Esa; Salmy Edawati Yaacob; Hairunnizam Wahid (Bulletin of Islamic Research, 2025)
This study addresses the absence of structured Shariah audit mechanisms in zakat institutions, particularly in the operational aspects of zakat distribution. Hence, the objective of the study is to develop Shariah audit criteria grounded in authoritative references such as fatwas, governance manuals, and Islamic finance standards. Adopting a qualitative document analysis approach guided by the Logical Framework model, this study systematically translates key Shariah principles into practical audit criteria. The findings aim to enhance Shariah assurance, improve institutional accountability, and support more consistent zakat governance practices across decentralized systems. This study presents the development of Shariah audit criteria for zakat distribution by integrating documentary sources such as fatwas, governance standards, and institutional SOPs with practical operational considerations. Key findings include a structured set of audit criteria rooted in principles such as comprehensiveness, prioritisation, and data completeness, which were translated into actionable audit tools. The study also identifies critical enablers such as trained personnel, dedicated Shariah committees, and supportive digital systems that are necessary for effective Shariah auditing. Discussions highlight three key governance gaps: the lack of structured Shariah oversight mechanisms, limited legal institutionalisation of Shariah functions, and insufficient stakeholder competency. The study calls for the establishment of a formal Shariah governance framework, aligned with national enactments and supported by a Shariah Audit Competency Framework. Overall, this research contributes to institutionalising Shariah auditing as both a compliance and strategic governance tool in zakat management, fostering transparency, accountability, and public trust in line with the maqasid of zakat.